Novel 2, 4-disubstituted quinazolines as cytotoxic agents and JAK2 inhibitors: Synthesis, in vitro evaluation and molecular dynamics studies. (April 2019) - Jyothi Buggana, Siva; Paturi, Mani Chandrika; Perka, Harathi; Gade, Deepak Reddy; VVS, Rajendra Prasad
Graphical abstract: Highlights: Present investigation focused on identification of novel quinazolines for cytotoxic and JAK2 inhibitory activities. Considerable In vitro cytotoxic potentials were reported against selected human (and non-human) cancer cell lines. In vitro JAK2 inhibition studies elucidated the mechanistic profile of the derivatives with moderate percentage of inhibition. Conformational changes of quinazolines in JAK2 protein environment is elucidated through molecular dynamics simulations. Abstract: Recent studies reported the involvement of JAK2/STAT3 pathway in various solid tumours including breast, ovarian, prostate and lung cancers. Clinical literature also reported the lowered burden in breast and ovarian cancers by targeting JAK2 pathway. In this study, a series of novel 2, 4-disubstituted quinazolines (2a-2 j and 3a-3 j) were synthesized and were evaluated for their cytotoxicity against human breast cancer (MDA-MB-231) and ovarian cancer (SK-O-V3) cell lines using MTT assay. Moderate to good in vitro cytotoxic potentials of the newly synthesized molecules were reported against selected human cancer cell lines. Among the tested molecules, compound3b has shown better cytotoxic activity against MD-MB-231 (10.1 ± 0.51 μM). in vitro JAK2 inhibition assay elucidated the mechanistic profile of the derivatives with moderate percentage of inhibition. Compounds3b and3d were reported with 35.4% and 34.2% inhibition of JAK2 protein. SAR studies suggest that the larger hydrophobic aromatic nucleus with hydrophilic linkage could probably increase the cytotoxic and JAK2 potentials and hydroxyl or nitro substitution could be more beneficial. Molecular dynamics simulation studies with JAK2-3b, and JAK2-3d complexes elucidated the conformational changes. With the reported bioactivities of these derivatives, further studies on the derivatization could elucidate the broader cytotoxic potentials.